Yizani Sifunde: Impact beyond the classroom: shifts in homes and communities - von Blottnitz, Magali (Liberty Community Trust, Wordworks, Book Dash and Nal'ibali, 2024)
This is the fifth in a series of learning briefs that explore the design, implementation and impact of Yizani Sifunde, a collaborative multi-pronged intervention designed to boost early literacy outcomes in 4- and 5-year-olds. This brief focuses on: • the elements of the project that targeted the homes of the children, as well as some community stakeholders, namely distribution of abundant children's books for the children to own at home; caregiver workshops; reading clubs and community activations. • the shifts that resulted for these groups, using the Home Learning Environment (HLE) tool from the DataDrive2030 suite; and • how these legs of the intervention consolidated or extended the project’s impact on young children. The HLE data reveals that the project resulted not only in a considerable increase in the number of books available in the homes, but also in increased caregiver reading behaviour. At endline, almost all caregivers claimed to read to their children at least once weekly. Qualitative data revealed that three effects ("nudge effect", "joy and pride effect" and "skill and confidence effect") enabled the shift of the caregivers' reading behaviour. Caregivers also became more involved in the life of the ECDs. In addition, caregivers who attended parent workshops became more involved in a number of other activities with their children, such as storytelling or drawing. These experiences at home helped the children strengthen and consolidate the benefits from improved classroom practices. The brief also reviews and discusses the project's experience with running reading clubs, and find that reading clubs led by the project's staff or by partner institutions were more successful and operated in a more consistent manner than reading clubs run by community volunteers. These additional project activities helped to extend the project's reach to a wider number of children, in particular children in primary schools or young children who were not attending ECD centres.
Exploring the impact of a collaborative, multi-pronged early literacy intervention on 4- and 5-year-olds - Brief 5
Yizani Sifunde (isiXhosa for “come, let’s read”) aimed to boost early literacy outcomes at under-resourced early childhood development (ECD) centres in the Eastern Cape. It was implemented in three one-year cycles between 2021 and 2023. The project was initiated and funded by the Liberty Community Trust, and jointly designed and delivered by three literacy nonprofits: Book Dash, Nal’ibali and Wordworks. Local Eastern Cape partners ITEC and Khululeka supported implementation. Social Impact Insights Africa carried out the external evaluation. More information on the Yizani Sifunde project can be found on https://bookdash.org/yizani-sifunde/ This Learning Brief was written for the Yizani Sifunde project by Dr Magali von Blottnitz, with input from other project partners. It draws extensively on an external evaluation conducted by Social Impact Insights Africa. Liberty Community Trust holds the intellectual property rights to the evaluation results and gave permission for them to be shared subject to specific acknowledgements.
Keywords: Early learning; Early literacy; Early Childhood Development; Yizani Sifunde; South Africa; Eastern Cape; ECD centres; Liberty Community Trust; Wordworks; Nal'ibali; Book Dash; Khululeka; ITEC; Pre-Grade R; Impact Evaluation; Collaboration; Caregiver workshops; Parents; Home Learning Environment; Triple-Cocktail approach; Children's Books; Book ownership; Every Word Counts; EWC; Story Sparkers; Reading Clubs; Reading; Social Impact Insights Africa